Method for evaluating compatibility between coals, method for predicting coke quality, method for producing coke, and method for obtaining solubility parameter of coal
By evaluating coal compatibility using Hansen solubility parameters, the method addresses the inaccuracies in existing coke strength prediction methods, enabling precise and efficient production of high-strength coke.
Patent Information
- Application Number
- JP2024090257
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-06-07
- Filing Date
- 2024-06-03
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2044-06-03
AI Technical Summary
Existing methods for predicting coke strength using vitrinite average maximum reflectance (Ro) and maximum fluidity (MF) often deviate from actual coke strength, and methods based on surface tension are complex and time-consuming.
Evaluating the compatibility between coals using Hansen solubility parameters to predict coke strength by determining the distance between the solubility parameters of blended coals, and selecting coals with specific parameter differences to achieve high strength.
Enables accurate and efficient prediction of coke strength by ensuring high compatibility between coals, leading to stable production of high-strength coke.
Smart Images

Figure 2024177103000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for evaluating compatibility between coals, a method for predicting coke quality, a method for producing coke, and a method for obtaining the solubility parameter of coal. [Background technology]
[0002] Coke is produced by crushing coal to a specified particle size and then heating the crushed coal in an oxygen-free atmosphere in a carbonization furnace. To stabilize the quality of the coal, a blend of multiple coal brands is used.
[0003] The coke produced in this way functions as a reducing agent for iron ore, a source of carburization, and a heat source in the blast furnace. The porous structure of the coke ensures the gas permeability and liquid permeability of the blast furnace. Therefore, the coke needs to have a high strength so that it does not crumble or break down during transportation and charging into the blast furnace.
[0004] The strength of coke is greatly affected by the properties of the coal used as raw material.
[0005] Therefore, various methods have been considered for predicting the strength of coke obtained by carbonizing a coal blend based on the physical properties of the coal used in the coal blend.
[0006] Conventional techniques include a method that uses the average maximum vitrinite reflectance (hereinafter sometimes referred to as Ro) of coal or the maximum fluidity (hereinafter sometimes referred to as MF) measured by the Gieseler Plastometer method. It is empirically known that these physical properties of coal are related to the strength of coke after carbonization. Therefore, attempts have been made to predict coke strength by creating a regression equation using the Ro and MF of each coal brand selected as a coke raw material and accumulated operational data.
[0007] Patent Document 1 also discloses a method for determining the surface tension (hereinafter sometimes referred to as γ) of semi-coke obtained by heat treating coal, and evaluating the adhesiveness between coal particles based on the difference in surface tension (hereinafter sometimes referred to as Δγ). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] International Publication No. 2013 / 145677 [Non-patent literature]
[0009] [Non-Patent Document 1] Julio C. Zuaznabar-Gardona et al., Journal of Molecular Liquids 294 (2019) 111646 [Non-Patent Document 2] Takabayashi et al. Journal of Petroleum Technology Vol. 85 No. 2 p.124-128(2020) [Non-Patent Document 3] Hiroshi Yamamoto et al. Chemical Industry Vol. 61 No. 4 p. 310-317 (2010) Summary of the Invention [Problem to be solved by the invention]
[0010] It has been known that when attempts are made to predict coke strength using the Ro or MF, the actual coke strength often deviates from the prediction.
[0011] Also, attempts have been made to evaluate the adhesiveness between coals from the surface tension using the method of Patent Document 1, and to predict coke strength based on the adhesiveness. However, this method has problems in that the experimental procedures are complicated and the measurement takes a long time.
[0012] The present invention has been made in view of the above circumstances, and has an object to provide a method for evaluating the compatibility between coals that enables prediction of coke strength simply and with high accuracy, and a method for acquiring the solubility parameter of coal that can be used in the method for evaluating the compatibility between coals. [Means for solving the problem]
[0013] The gist of the present invention for solving the above problems is as follows.
[0014] [1] A method for evaluating compatibility between two types of coal, comprising the steps of: Obtaining the solubility parameters of the two types of coal; A method for evaluating compatibility between coals, comprising: evaluating compatibility between the two types of coal based on a distance between the solubility parameters of the two types of coal.
[0015] [2] The method for evaluating compatibility between coals according to [1] above, wherein the solubility parameter is a Hansen solubility parameter.
[0016] [3] The method for evaluating compatibility between coals according to any one of [1] to [2] above, wherein the two types of coal are heat-treated before obtaining the solubility parameters.
[0017] [4] A method for predicting coke quality, comprising predicting coke quality based on coal compatibility evaluated using the method for evaluating coal compatibility according to any one of [1] to [3] above.
[0018] [5] A method for producing coke, comprising determining a coal blend based on compatibility between coals evaluated using the method for evaluating compatibility between coals according to any one of [1] to [3] above.
[0019] [6] A coke manufacturing method, comprising determining a coal blend based on the coke quality predicted by the coke quality prediction method described in [4] above.
[0020] [7] A method for obtaining the solubility parameter of coal, comprising the steps of: Molding the coal into tablets; The tablet is permeated with a solvent and the permeation time is measured; determining an affinity between the coal and the solvent based on the permeation time; A method for obtaining the solubility parameter of coal, comprising deriving the solubility parameter based on the affinity.
[0021] [8] The method for obtaining the solubility parameter of coal described in [7], wherein the coal is heat-treated before obtaining the solubility parameter.
[0022] [9] A method for producing coke according to the above [5], The solubility parameter is the Hansen solubility parameter, In determining the blending ratio, for all combinations of two types of coal to be blended, The distance ΔHSP between the Hansen solubility parameters is 12.3 (MPa) 0.5 less than and selecting the coals to be blended so that the blended coals satisfy the above conditions.
[0023]
[10] A method for producing coke according to the above [5], The solubility parameter is the Hansen solubility parameter, In determining the blending ratio, for all combinations of two types of coal to be blended, The absolute value of the difference between the common logarithm values of the maximum flow rate measured by the Gieseler Plastometer method, ΔLogMF, is 0.67 log / ddpm or less. The absolute value of the difference in the average maximum reflectance of vitrinite, ΔRo, is 0.05% or more, and The distance ΔHSP between the Hansen solubility parameters is 4.2 (MPa) 0.5 below and selecting the coals to be blended so that the blended coals satisfy the above conditions. Effect of the Invention
[0024] According to the present invention, a method for evaluating compatibility between coals can be provided, and based on the method, coke strength can be predicted easily and with high accuracy. In addition, a method for acquiring solubility parameters of coals that can be used in the method for evaluating compatibility between coals can be provided. [Brief description of the drawings]
[0025] [Figure 1] FIG. 2 is a graph showing the relationship between the density and crushing strength of carbonized pelletized coke. [Diagram 2] 1 is a graph showing the relationship between ΔHSP and the crushing strength of coke. [Diagram 3] 1 is a graph in which the weighted average intensity and the intensity obtained by actual measurement are plotted against ΔHSP. [Figure 4] 1 is a graph showing the relationship between bulk density and crushing strength of coke. [Diagram 5] 3 is a graph comparing the predicted intensity based on the regression line obtained from FIG. 2 with the predicted intensity based on the regression equation of multiple regression analysis. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] Hereinafter, examples of embodiments of the present invention will be described in detail. Note that the following description is merely illustrative of the embodiments of the present invention, and the present invention is not limited to the following embodiments.
[0027] [Compatibility between coals] As mentioned above, coke is obtained by carbonizing coal. During this process, coal becomes soft and molten, and then the soft and molten coal resolidifies with foaming. The property of coal melting together when it becomes soft and molten is called the compatibility between coals.
[0028] If the compatibility between coals is low, the coals in a softened and molten state will not mix together. As a result, interfaces will remain in the coke when it resolidifies. At this time, cracks will occur at the interfaces, reducing the strength of the coke. Therefore, in order to produce high-strength coke, it is necessary to select coal brands that have high compatibility between the coals and blend them as raw materials.
[0029] [Solubility parameters] The solubility parameter (hereinafter, also referred to as SP) is an index of the surface state calculated from the molecular structure and surface energy. Substances with similar solubility parameters dissolve well together because they have similar surface conditions.
[0030] The inventors came up with the idea of using solubility parameters to evaluate the compatibility between coals. By blending coals with similar solubility parameters, the coals melt well together during the softening and melting process during carbonization, making it possible to obtain coke with higher strength. In other words, by using the solubility parameters of coals, it is possible to predict coke strength and determine the coal blending required to obtain high-strength coke.
[0031] The method of expressing the solubility parameter is not particularly limited, and a preferred index such as a point in a four-dimensional orthogonal coordinate system, a point in a three-dimensional orthogonal coordinate system, a point in a two-dimensional orthogonal coordinate system, or a one-dimensional numerical value may be adopted. However, by increasing the number of dimensions of the solubility parameter, more factors that determine the surface state of coal in a softening and melting state can be reflected, and the surface state can be compared in more detail. From this viewpoint, it is preferable that the solubility parameter is expressed as a point in a multidimensional orthogonal coordinate system. Furthermore, since the number of dimensions of the solubility parameter is three, it is possible to fully reflect the factors that determine the surface state, and it is also possible to perform coordinate geometric evaluation using the dissolving sphere method described later. From this viewpoint, it is more preferable that the solubility parameter is expressed as a point in a three-dimensional orthogonal coordinate system. Hereinafter, the three-dimensional orthogonal coordinate system may simply be referred to as a three-dimensional space. Furthermore, the solubility parameter expressed as a point in the three-dimensional space may be referred to as a three-dimensional SP.
[0032] Solubility parameters include, but are not limited to, the Hildebrand solubility parameter, which is expressed as a one-dimensional numerical value, and the Hansen solubility parameter (hereinafter sometimes referred to as HSP), which is a three-dimensional SP. Herein, the HSP is a solubility parameter expressed as a point in a three-dimensional space with the dispersion force term (δD), the polarization term (δP), and the hydrogen bond term (δH) as axes. Hereinafter, the three-dimensional space with the axes δD, δP, and δH may be referred to as the Hansen space.
[0033] Among the three-dimensional SPs, the HSP has a more extensive database than other solubility parameters. By using this database, the solubility parameter of coal can be easily derived using many solvents, and the accuracy of the solubility parameter of coal is improved. Therefore, the solubility parameter is preferably the HSP.
[0034] Solubility parameters other than those mentioned above include solubility parameters derived by correcting at least one of the three terms of HSP based on HSP. In this case, the solubility parameter after correction may be a three-dimensional SP, or a solubility parameter other than the three-dimensional SP. A specific example of the correction is to divide δH into a donor term and an acceptor term. The solubility parameter derived by this correction is expressed as a point in a four-dimensional orthogonal coordinate system with δD, δP, the donor term, and the acceptor term as axes.
[0035] The distance between solubility parameters is the absolute value of the difference between two solubility parameters when the solubility parameters are expressed as one-dimensional numerical values, and is the distance between two points in a multidimensional orthogonal coordinate system when the solubility parameters are expressed as points in the multidimensional orthogonal coordinate system.
[0036] The present invention will be described below based on specific embodiments. Note that in the following embodiments and examples, the solubility parameter is mainly HSP, but as described above, the present invention is applicable to any solubility parameter, not limited to HSP.
[0037] First embodiment In the first embodiment of the present invention, compatibility between two types of coal is evaluated.
[0038] [Method for evaluating compatibility between coals] According to the present invention, the compatibility between two types of coal can be evaluated by the following procedure. Step (1): Acquire the solubility parameters of the coals. At this time, the solubility parameters of the two types of coals may be acquired separately or simultaneously. Step (2) Evaluate the compatibility between coals based on the distance between the two obtained solubility parameters.
[0039] [Step (1): Procedure for obtaining the solubility parameter of coal] The procedure for acquiring the solubility parameter of coal according to the present invention will be described below.
[0040] This procedure (1) includes, for example, the following operations: Procedure (A): Determine the affinity of coal with a reference substance. Step (B): Derive the solubility parameter of coal based on the affinity.
[0041] In particular, when the solubility parameter is a three-dimensional SP, the dissolving sphere method described below can be suitably used in the step (B).
[0042] [Step (A): Step for determining affinity] In this procedure, the affinity of coal with a reference material is determined using a unified criterion.
[0043] In the present invention, a solvent is used as the reference substance. The type of solvent to be used is not limited, but it is preferable to use a low-molecular pure solvent since a database of solubility parameters exists.
[0044] The number of types of solvents is preferably multiple, more preferably 10 or more, and even more preferably 15 or more. By selecting more solvents, the accuracy of deriving the solubility parameter can be increased.
[0045] In addition, it is preferable to select the plurality of types of solvents so that they are composed of solvents with various physical properties. For example, it is preferable to select from a wide variety of solvents, such as water and aqueous solutions having hydrogen bonds, nonpolar organic solvents, and polar organic solvents. Examples of nonpolar organic solvents include hydrocarbon-based organic solvents. Examples of polar organic solvents include organic solvents having functional groups such as formyl groups, carbonyl groups, hydroxyl groups, or amino groups. This allows the affinity between coal and solvents with different solubility parameters to be evaluated, improving the accuracy of deriving the solubility parameter of coal. For example, when HSP is used as the solubility parameter, the values of δP and δH vary greatly from solvent to solvent, so these values can be dispersed by selecting solvents with various physical properties.
[0046] More specifically, it is preferable to use a plurality of types of solvents selected so as to include at least one of the following (a), (b), and (c): (a) Water or an aqueous solution (b) Non-polar organic solvent (c) Polar organic solvent Alternatively, one or more mixed solvents obtained by mixing two or more miscible solvents at any ratio may be used as the solvent. In this case, the value of each term of the solubility parameter of the mixed solvent can be determined as a weighted average calculated from the value of the corresponding term of the solubility parameter of the mixed solvent and the mixing ratio. Since the solubility parameter of the mixed solvent can be adjusted by adjusting the mixing ratio, the use of the mixed solvent makes it easy to disperse the solubility parameter.
[0047] Furthermore, when using 3D SP as the solubility parameter, it is advisable to select the solvent so that the 3D SP of the solvent is appropriately dispersed in 3D space, which allows the 3D SP of coal to be derived more precisely using the dissolving sphere method.
[0048] In particular, when using HSP as the solubility parameter, it is advisable to select solvents so that the δH of each solvent is evenly distributed within the expected numerical range of δH for coal and its surrounding areas. This is for the following reasons. First, δH is a component derived from hydrogen bonds, and therefore in coal it is thought to be related to functional groups such as hydroxyl and carboxyl groups at the molecular ends. Furthermore, since these functional groups often cause condensation and elimination due to changes in the skeletal structure of the carbon content caused by dry distillation, δH is thought to be a term that particularly affects the molecular structure of the sample being measured.
[0049] When determining the affinity between coal and the solvent, it is difficult to determine the affinity based on the presence or absence of dissolution because coal is black. Therefore, as a specific method of step (A), the penetration time method or the dispersion method described below can be used. In addition to the above methods, there is also a method in which the value of the wetted area or the contact angle is used to check whether the solvent has wettability to coal, and the affinity is determined based on the wettability.
[0050] [Penetration time method] This method involves dropping a solvent onto a tablet formed from coal, and judging the affinity of the coal with the solvent based on the time required for the solvent to penetrate. Advantages of this method include simple experimental procedures and a short time required. Furthermore, since the experimental procedures are simple, there is also the advantage that anyone can perform measurements with high accuracy, without the need for an expert. For example, when determining surface tension using the method described in Patent Document 1 and predicting coke strength by evaluating adhesion between coals from the surface tension, the experimental procedures are complicated. In particular, when measuring surface tension using the film flotation method, the operation of dropping coal particles onto the surface of the liquid must be performed accurately, so the experimental procedures are significantly more complicated, and it takes time due to the large number of steps. In contrast, the method of judging affinity and evaluating compatibility between coals using the penetration time method involves simple experimental procedures. Furthermore, if the penetration time method is used, the measurement time can sometimes be reduced to within 1 to 2 minutes, making it possible to shorten the measurement time compared to other methods of judging affinity. The specific steps of this method are described below.
[0051] (Crushing) It is preferable to crush the coal during the molding. Although the crushing process is optional, crushing can reduce the particle size of the coal, and the distribution of voids becomes uniform when the tablet is molded. This allows the permeation time to be measured more accurately.
[0052] (molding) The coal is then molded into tablets.
[0053] The particle size of the coal used in the molding is not particularly limited. However, from the viewpoint of using coal with adjusted particle size, the particle size of the coal is preferably 150 μm or less, more preferably 50 μm or less. Note that the particle size of the coal is X μm or less means that all the coal particles pass through a sieve with an opening of X μm, and the particle size of the coal is more than Y μm means that all the coal particles remain on a sieve with an opening of Y μm.
[0054] Any molding method can be used, but a suitable molding method is to fill the coal in a mold and pressurize it to produce tablets. Examples of the shape of the tablet include cylindrical and rectangular shapes. Here, the shape is preferably a shape having a flat surface as a drip surface. In addition, from the viewpoint of being able to apply pressure more evenly during pressurization, the shape is more preferably cylindrical.
[0055] There is no particular restriction on the molding conditions, but in order to make the density distribution more uniform and improve the accuracy of the measurement, it is preferable that the molding pressure is 100 MPa or more. For the same reason, it is preferable that the height of the tablet is 5 mm or more and 15 mm or less. Also, for the same reason, it is preferable that the tablet is cylindrical and the diameter of the molded body is 10 mm or more and 20 mm or less. Furthermore, it is preferable that the mass of the tablet is 0.5 g or more and 2.0 g or less.
[0056] (Solvent penetration) Next, the molded tablet is permeated with the solvent to measure the permeation time. The permeation can be performed by dropping the solvent onto the tablet. By increasing the amount of solvent dropped, the time until the permeation is completed is extended, and the affinity between the coal and the solvent can be accurately determined. Therefore, the amount of the dropped solvent is preferably 2 μL or more. On the other hand, in order to prevent variation in the permeation time due to the influence of wetting and spreading, the amount of the dropped solvent is preferably 10 μL or less.
[0057] The method for measuring the permeation time is not particularly limited, and the time taken for the solvent to disappear from the tablet surface may be observed with the naked eye.
[0058] (Affinity determination) Finally, the affinity between coal and the solvent is judged based on the permeation time. Specifically, when the permeation time is equal to or less than a reference value, the affinity is judged to be "good", and when the permeation time exceeds the reference value, the affinity is judged to be "bad". The reference value can be arbitrarily determined based on the type of solvent dropped or the experimental results, but from the viewpoint of further improving the accuracy of derivation of the solubility parameter, it is preferable to determine it based on the ratio of the number of solvents judged to be good to the total number of solvents. Specifically, the reference value is preferably set so that the ratio is 25% or more, and more preferably set so that the ratio is 35% or more. Moreover, the reference value is preferably set so that the ratio is 75% or less, and more preferably set so that the ratio is 65% or less.
[0059] [Dispersion method] This method involves dropping a solvent onto coal, shaking the container containing the coal and solvent, and then determining the state of suspension in the container after the container is left to stand. The advantage of this method is that the experimental procedure is very simple, since it only involves stirring the coal and solvent and leaving them to stand. From the perspective of the complexity of the procedure, this is a simpler measurement method than other methods for determining affinity. Another advantage is that the experimenter does not need to have skilled techniques, and anyone can perform measurements with high accuracy. The specific steps of this method are described below.
[0060] First, it is preferable to crush the coal, since by making the coal finer, the coal is more easily dispersible in the solvent and the measurement accuracy is improved. The coal before the solvent is dripped has a particle size of preferably 150 μm or less, more preferably 100 μm or less.
[0061] The methods of dropping, shaking, and standing are not particularly limited, and can be any method.
[0062] The state of the liquid in the container after being left to stand is checked, and if it maintains a suspended state, it is judged to have "good" affinity. If the coal powder has completely settled or floated, the liquid has become transparent, and the coal and the solvent have been separated, it is judged to have "bad" affinity. There are no particular limitations on the method for checking the state of the liquid, and it may be checked with the naked eye or using a measuring device. When using a measuring device, for example, an absorbance meter or a turbidity meter may be used, and a judgment may be made from the change in measurement data over time.
[0063] [Step (B): Procedure for deriving the solubility parameter of coal] In this procedure, the solubility parameter of coal is derived based on the affinity determined in the above procedure (A).
[0064] In the derivation, the derivation method can be appropriately determined so that the distance from the solubility parameter of a reference substance having an affinity of "good" is close and the distance from the solubility parameter of a reference substance having an affinity of "bad" is far.
[0065] The method of acquiring the solubility parameter of the reference substance is not particularly limited. Suitable methods include a method of acquiring the solubility parameter by calculation from the molecular structure and a method of acquiring the solubility parameter by referring to a database. However, many of the solubility parameters described in the database are corrected in various ways according to the actual system, and even a specific reference substance may have different solubility parameters depending on the reference source. Therefore, using two or more types of databases at the same time may cause errors in the solubility parameter of the coal to be derived. Therefore, when acquiring the solubility parameter of the reference substance by referring to a database, it is preferable to use the same database for the two types of coal whose compatibility is to be evaluated.
[0066] Furthermore, when the solubility parameter is a three-dimensional SP, the dissolving sphere method can be suitably used in this step (B).
[0067] Generally, the solubility parameter is calculated from the molecular structure. However, since the molecular structure of coal is amorphous, it is impossible to directly calculate the solubility parameter. Therefore, by using the molten sphere method, it is possible to indirectly derive the 3D SP of coal through geometric analysis.
[0068] In step (B) of the dissolved sphere method, first, an inscribed sphere is drawn in a three-dimensional space, which includes points corresponding to the three-dimensional SP of the reference material judged as "good" in the affinity judgment in step (A) above, but does not include points corresponding to the three-dimensional SP of the reference material judged as "bad." The central coordinates of the inscribed sphere are then taken as the three-dimensional SP of the coal.
[0069] The method of drawing the inscribed sphere and the method of deriving the center coordinates are not particularly limited. Suitable methods include a method using manual calculation and a method using software.
[0070] Although step (1): the step of acquiring the solubility parameter of coal has been described above, there is no limitation on the timing of acquiring the solubility parameter when evaluating compatibility between coals. In other words, when evaluating compatibility multiple times, it is not necessary to derive the solubility parameter each time, and as long as the solubility parameter has been acquired in advance for one or both of the coals for which compatibility is to be evaluated, it can be used to perform step (2) described below.
[0071] [Step (2): Procedure for evaluating compatibility between coals] The procedure for evaluating compatibility between coals according to the present invention will be described below.
[0072] In this procedure, the compatibility between coals can be evaluated by calculating the distance between the solubility parameters of the coals obtained in procedure (1) above.
[0073] For example, the distance between the solubility parameters can be used as a value of compatibility between coals, where the closer the distance, the higher the compatibility.
[0074] By evaluating the compatibility between coals in this way, it is possible to correctly evaluate the fusibility of coals in a soft and molten state. This will improve the accuracy of estimations for obtaining high-strength coke, optimize coal blending guidelines, and increase the efficiency of operations. Furthermore, it is expected that the selection of appropriate brands will contribute to stable production.
[0075] Second Embodiment In a second embodiment of the present invention, the two types of coal are heat-treated before acquiring the solubility parameter by the procedure (1). In other words, each of the two types of coal used in the procedure (1) is a coal that has been heat-treated before acquiring the solubility parameter.
[0076] (Heat treatment) This step is optional. However, by subjecting the coal to a heat treatment, the coal can be brought closer to a thermoplastic state, which improves the accuracy of the compatibility evaluation. For this reason, it is preferable that the coal is heat-treated before acquiring the solubility parameter.
[0077] From the viewpoint of bringing the coal closer to a plastic and molten state, the heat treatment is preferably carried out in an oxygen-free atmosphere. For the same reason, the heat treatment temperature is preferably 350 to 800°C. Coal that has been subjected to the heat treatment in an oxygen-free atmosphere at a temperature of 350 to 800°C is called semi-coke. It is more preferable that the two types of coal are made into semi-coke before the solubility parameter is obtained.
[0078] The procedure after the heat treatment is the same as in the first embodiment.
[0079] Third embodiment In the method for predicting coke quality according to the third embodiment of the present invention, the compatibility of coals is evaluated based on the method for evaluating compatibility between coals according to the present invention, and the quality of coke is predicted based on the compatibility.
[0080] For example, if there are n coals used as raw materials for coke, the compatibility between two coals is evaluated by using a combination of two of the n coals. n The method is carried out in the manner of C2. The coal used for the compatibility evaluation may be heat-treated coal. Then, a correction is made to the conventional prediction formula for coke strength by adding a term having the compatibility evaluation result as a variable. By using the corrected prediction formula, the quality of the coke can be predicted with high accuracy.
[0081] As another example, the solubility parameters of incoming coal are calculated one after another and compared to predict the quality of coke. This allows early detection and correction of any quality fluctuations from batch to batch.
[0082] (Fourth embodiment) The coke production method according to the fourth embodiment of the present invention includes a step of determining a coal blending based on the compatibility between coals evaluated using the method for evaluating coal compatibility according to the present invention. In other words, the coke production method according to the fourth embodiment of the present invention is a coke production method in which the coal blending is determined based on the compatibility between two types of coal evaluated using the above-mentioned method for evaluating coal compatibility.
[0083] In the above step, the blend of coals that can obtain high coke strength can be determined by taking into consideration the compatibility evaluation results. The coal used in the compatibility evaluation may be heat-treated coal.
[0084] For example, the process is a process of determining rules so that when two types of coal brands are selected from among the candidate raw material coal brands, the distance between the solubility parameters is equal to or less than a certain value (or less than a certain value), and selecting coal in accordance with the rules. This makes it possible to stably produce high-strength coke. The solubility parameter is HSP (unit: (MPa) 0.5), the distance ΔHSP between HSPs is preferably less than 12.3. In other words, in determining the blending, it is preferable to select the coals to be blended so that ΔHSP is less than 12.3 for all combinations of two types of coal to be blended. This further improves the strength of the adhesive interface between different brands, and as described in detail in the examples, it is possible to produce a coke with a strength higher than the weighted average strength of a coke made from a single coal. ΔHSP is more preferably 7.0 or less, and even more preferably 4.2 or less. In addition, in order to produce a coke with higher strength, additional rules may be established to select the coals. For example, it is considered that the closer the physical property values of the blended coals are, the higher the strength of the coke produced will be. Therefore, in selecting the coals, it is preferable to set the absolute value ΔLogMF of the difference between the common logarithm values of MF to a certain value or less (or less than a certain value). However, from the viewpoint of balancing with other physical property values, the greater the difference in the physical property values of the blended coals, the higher the strength of the coke may be obtained. Therefore, for example, the absolute value ΔRo of the difference between Ro may be set to a certain value or more (or more than a certain value). In particular, in determining the blending, it is preferable to select the coals to be blended so that all of the combinations of two types of coal to be blended satisfy all of the following conditions (1) to (3). (1) ΔLogMF is 0.67 log / ddpm or less (2) ΔRo is 0.05% or more (3) ΔHSP is 4.2 or less This allows production of coke with higher strength, as will be described in detail in the Examples.
[0085] As another example, the process is a process of selecting a substitute coal for a particular brand, which has a close distance between the solubility parameters, thereby minimizing the change in quality of the coke due to a change in brand.
[0086] The bulk density of the coke to be produced is not particularly limited. However, if the bulk density is too low, the macroscopic strength may be reduced. Therefore, the bulk density is set to 0.82 g / cm. 3On the other hand, when a multiple regression analysis is performed on two-brand blended coal with the ΔLogMF, ΔRo, and ΔHSP of the blended coal and the bulk density of the obtained coke as explanatory variables and the coke strength as the objective variable, there are cases where the bulk density has a negative correlation with the strength. In other words, a high bulk density may conversely result in a low strength, so the bulk density is preferably 0.92 g / cm 3 It may be the following.
[0087] Fifth embodiment The coke production method in the fifth embodiment of the present invention includes a step of determining a blend of coal brands based on the coke quality predicted by the coke quality prediction method according to the present invention.
[0088] Sixth Embodiment A method for acquiring the solubility parameter of coal in a sixth embodiment of the present invention is a method for determining the affinity between coal and a solvent based on the penetration time method, and deriving the solubility parameter of the coal based on the affinity. The derivation is preferably performed by the procedure (B).
[0089] Seventh embodiment In the method for acquiring the solubility parameter of coal in the seventh embodiment of the present invention, the heat treatment is performed on the coal before the affinity between the coal and the solvent is determined by the permeation time method. In other words, the coal used in the permeation time method is the coal that has been subjected to the heat treatment before acquiring the solubility parameter.
[0090] The procedure after the heat treatment is the same as in the sixth embodiment. EXAMPLES
[0091] Hereinafter, an application method of the present invention will be described based on an example of the following embodiment, however, the present invention is not limited to this embodiment.
[0092] [Acquisition of HSP for coal] First, the common logarithm of Ro and MF (hereinafter sometimes referred to as LogMF) of each coal shown in Table 1 was measured to obtain the values shown in Table 1. The Ro was determined by a method in accordance with JIS M 8816. The LogMF was determined by a method in accordance with JIS M 8801.
[0093] [Table 1]
[0094] Next, the HSP of each coal listed in Table 1 was determined using the above-mentioned dispersion method.
[0095] Coal of brand A in Table 1 was crushed to 44 μm or less, and 10 mg of the crushed coal was weighed for each solvent to be dropped and separated into vials. Next, 5 mL of the solvent listed in Table 2 was dropped into each vial, and the vials were left to stand for 30 minutes after shaking thoroughly. The state of the liquid in the container after the standing was visually confirmed, and those that maintained a suspended state were judged to have a good affinity. In addition, those in which the coal powder had completely settled or floated, the liquid part had become transparent, and the coal and the solvent had separated were judged to have a bad affinity. Then, the HSP listed in Table 2 for the solvent judged to have a good affinity was expressed as a point in Hansen space, and the central coordinates of the inscribed sphere containing those points were taken as the HSP of that coal.
[0096] The same procedure was carried out for coals other than brand A in Table 1, and the HSPs of the coals listed in Table 3 were obtained.
[0097] [Table 2]
[0098] [Table 3]
[0099] From the values in Tables 1 and 3, three types of indices ΔRo, ΔLogMF, and ΔHSP were derived for the combinations shown in Table 4. ΔRo and ΔLogMF are the absolute values of the differences between Ro and LogMF, respectively. ΔHSP is the HSP distance, and is used in this embodiment as a value indicating the compatibility between coals.
[0100] [Table 4]
[0101] The HSP values in Table 2 are based on the descriptions in Non-Patent Documents 1 to 3, and the units of the HSP items in Tables 2 and 3 and ΔHSP in Table 4 are (MPa). 0.5 It was decided.
[0102] [Observation of the coke interface] Next, the following experiment was carried out to evaluate the relationship between coal compatibility and coke quality.
[0103] Each of the coals listed in Table 1 was crushed to 150 μm or less. Next, for levels 1 to 4 of the combinations listed in Table 4, 0.5 mg of the crushed coal was packed in order into a cylindrical mold with a diameter of 13 mm. At this time, after packing the first brand, the surface was lightly smoothed with a pin before packing the second brand, thereby smoothing the interface. Then, press molding was performed for 3 minutes under a load of 5 t to produce two-layered pellets.
[0104] To suppress the influence of expansion, the pellets were sufficiently restrained with wires. Next, the pellets were heated from room temperature to 900°C at a heating rate of 3°C / min in a pure nitrogen atmosphere, held at that temperature for 10 minutes, and naturally cooled to obtain coke.
[0105] After carbonization, the coke still had an interface between the two types of coal. The coke was cut and the interface that appeared on the cut surface was observed with an optical microscope. Based on the observation results, the state of bubbles near the interface was evaluated. Table 5 shows the evaluation results of bubbles near the interface.
[0106] [Table 5]
[0107] Coal brand D is included in all combination levels 1 to 4, but is a coal that tends to foam after carbonization. If the compatibility in the combination is poor, the generation of homogeneous bubbles in coal brand D is hindered by the influence of the interface, which is thought to result in poor uniformity of bubbles near the interface and an increase in the amount of bubbles. It is thought that coke with poor bubbles near the interface is prone to cracking at the interface and has poor strength.
[0108] If each index listed in Table 4 is appropriate as an index for predicting the strength of coke, it is considered that there is a relationship in which the numerical value of the evaluation result of "good" level 4 is clearly lower than the numerical values of the evaluation results of "poor" levels 1 to 3. The above relationship was not confirmed with ΔRo, which is a conventional index. When ΔLogMF was used, the numerical values of ΔLogMF of "poor" level 3 and "good" level 4 were close, making it difficult to distinguish between good and bad, and the above relationship was not confirmed. On the other hand, when ΔHSP according to the present invention was used, it was possible to confirm the existence of the above relationship, and the difference in compatibility could be accurately evaluated. In other words, it is considered that the compatibility evaluation method according to the present invention makes it possible to accurately predict the strength prior to producing the coke.
[0109] [Strength test 1] Next, coals were blended in combinations 2 and 5 of Table 4, and the strength of the carbonized cokes was compared.
[0110] The three brands of coal that make up the above combinations were prepared and adjusted so that the particle size was greater than 74 μm and less than 1 mm. For coal brand D, twice the amount was prepared and divided equally for each combination. According to the above combinations, the coals were blended in a mass ratio of 1:1 and thoroughly mixed. Using each powdered blended coal, 20 cylindrical pellets of charcoal with a diameter of 10 mm and a height of about 10 mm were produced at a pressure of 100 MPa. Fifteen of these were carbonized in a heating furnace capable of controlling the atmosphere and flow rate. The carbonization was performed by heating the ambient gas from room temperature to 900 ° C at a rate of 3 ° C / min, holding it for 10 minutes, and then naturally cooling to room temperature while flowing nitrogen at the same flow rate. In addition, the tablets were placed in the furnace at a certain distance from each other so that they would not merge due to expansion during carbonization.
[0111] The mass, diameter, and height of each of the cokes produced by the carbonization were measured, and the density (bulk density) was calculated. Ten of the cokes were randomly selected, and the crushing strength was measured by a uniaxial compression test. The direction of the compressive load was the diameter direction of the cylinder of the coke, and the compression speed was 1 mm / min.
[0112] The measurement results are shown in Figure 1. In the graph of Figure 1, the X marks and circles correspond to the measurement results of the cokes using the coal blends of combinations 2 and 5, respectively, and the dashed and solid lines are linear approximations of the measurement points.
[0113] Factors that affect the strength of coke include not only the compatibility between coals but also the density of the coke. In fact, Figure 1 shows that for each coke made from two types of blended coal, the higher the density, the higher the strength. Therefore, by comparing cokes with the same density, it is possible to eliminate the effect of density and evaluate the effect of compatibility between coals on strength. In Figure 1, cokes with the same coke density (for example, 0.8 g / cm 3 ), it was found that level 5 was stronger than level 2.
[0114] As shown in Table 4, even if one tries to predict coke strength using ΔRo, which is a conventional index, it is difficult to predict that level 5 will show higher strength. However, by using ΔHSP according to the present invention, it is possible to predict that level 5 has better compatibility between coals and can produce a high-strength coke.
[0115] [Strength test 2] For each of the coal brands G to K, Ro and LogMF were measured by the above-mentioned method, and HSP was obtained by the above-mentioned method. The results are shown in Table 6. Three types of indices ΔRo, ΔLogMF, and ΔHSP were derived for the combinations shown in Table 7. The units of each item of HSP in Table 6 and ΔHSP in Table 7 are (MPa). 0.5 It was decided.
[0116] [Table 6]
[0117] [Table 7]
[0118] Next, coals were blended in the combinations shown in Table 7, and the strength of the carbonized coke was tested.
[0119] The five brands of coal that make up the above combinations were prepared and adjusted so that the particle size was 3 mm or less. According to the combinations 6 to 12 in Table 7, the coals were blended in a mass ratio of 1:1 and thoroughly mixed. Each powdered blended coal was fed into a carbonization furnace with a diameter of 100 mm and carbonized. The obtained coke was crushed to about 3 mm. The bulk density of the crushed coke was measured by a method conforming to JIS K 2151. In addition, the crushing strength of the crushed coke was measured using a Kiya hardness tester. In order to suppress the variation in the results so that the tendency of the results does not change, the crushing strength was measured 50 times, and the average was taken as the crushing strength of the coke.
[0120] The relationship between ΔHSP and coke crushing strength is shown in Figure 2. The dashed line is a linear approximation regression line. It was shown that the smaller the ΔHSP, the higher the strength. In addition, the regression line shown in Figure 2 can be used to predict the crushing strength based on ΔHSP.
[0121] Here, in order to investigate the effect of blending, that is, the influence of the strength of the adhesive interface between different brands, coke was produced from single coal and the strength was compared with that of coke produced from blended coal. If there is no effect of blending, it is considered that the strength of the coke produced from blended coal is the weighted average of the coke strengths derived from each single coal. First, coal G to K were carbonized in the same manner as levels 6 to 12 to obtain coke, and then a strength test was performed to obtain the strength of the coke produced from single coal. Figure 3 shows a graph plotting the weighted average strength and the strength obtained by actual measurement (actual value) for combinations 6 to 12 in Table 7 against ΔHSP. The solid line is a regression line linearly approximated to the actual measured value, and the dashed line is a regression line linearly approximated to the weighted average strength. It was shown that the smaller the ΔHSP of the combination, the higher the coke strength tends to be than the weighted average strength. From the obtained regression line, it is considered that when ΔHSP is less than 12.3, coke with a strength higher than the weighted average strength can be produced. In addition, it is considered that the difference between the weighted average strength and the actual coke strength can be further increased by setting ΔHSP to 7.0 or less.
[0122] Next, the relationship between bulk density and crushing strength of coke in combinations 6 to 12 in Table 7 is shown in Figure 4. Generally, the higher the bulk density, the higher the strength. 3 The increasing trend turned to a decreasing trend at the boundary. The levels at which low crushing strength was shown despite high bulk density all had large ΔHSP. In this way, when comparing coal blends made from different brands, the higher the coke density, the higher the coke strength. However, the distance between the solubility parameters can be used to predict coke strength even in such cases.
[0123] Furthermore, in order to improve the accuracy of strength prediction, multiple regression analysis was performed using ΔlogMF and ΔRo in addition to ΔHSP as explanatory variables and the crushing strength of the coke as the objective variable, resulting in the following regression equation. The coefficient of determination was high at 0.91, and the prediction accuracy was very good. I=a×ΔlogMF+b×ΔRo+c×ΔHSP+d Here, a = -0.66, b = 1.2, c = -0.38, d = 13.9, and I is the predicted value of the crushing strength of the coke. Figure 5 shows a comparison of the predicted strength (ΔHSP) using the regression line obtained from Figure 2 and the predicted strength using the regression equation of multiple regression analysis (multiple regression). It was shown that the predicted strength using the regression equation of multiple regression analysis was a more accurate value.
[0124] In addition, the combinations 10 to 12 in Table 7, which are shown to have particularly high compatibility and coke strength in Figures 2 and 3, all have ΔlogMF of 0.67 log / ddpm or less, ΔRo of 0.05% or more, and ΔHSP of 4.2 (MPa). 0.5 The correlation coefficient for the bulk density was confirmed to be negative when the multiple regression analysis was performed by adding the bulk density of the obtained coke to the explanatory variables. The combinations 10 to 12 in Table 7 all had a coke bulk density of 0.92 or less, so it was assumed that the bulk density was 0.92 g / cm3. 3 It is believed that if the temperature is below this range, coke with even higher strength may be produced.
Claims
1. 1. A method for assessing compatibility between two coals, comprising the steps of: Obtaining the solubility parameters of the two types of coal; A method for evaluating compatibility between coals, comprising: evaluating compatibility between the two types of coal based on a distance between the solubility parameters of the two types of coal.
2. The method for evaluating compatibility between coals according to claim 1 , wherein the solubility parameter is the Hansen solubility parameter.
3. The method for evaluating compatibility between coals according to claim 1 , wherein the two types of coal are heat-treated before the solubility parameters are obtained.
4. The method for evaluating compatibility between coals according to claim 2 , wherein the two types of coal are heat-treated before the solubility parameters are obtained.
5. A method for predicting coke quality, comprising predicting coke quality based on compatibility between coals evaluated using the method for evaluating compatibility between coals according to any one of claims 1 to 4.
6. A method for producing coke, comprising determining a blend of coals based on compatibility between coals evaluated using the method for evaluating compatibility between coals according to any one of claims 1 to 4.
7. A method for producing coke, comprising determining a coal blend based on the coke quality predicted by the method for predicting coke quality according to claim 5.
8. A method for obtaining a solubility parameter of coal, comprising the steps of: Molding the coal into tablets; The tablet is permeated with a solvent and the permeation time is measured; determining an affinity between the coal and the solvent based on the permeation time; A method for obtaining the solubility parameter of coal, comprising deriving the solubility parameter based on the affinity.
9. The method for acquiring a solubility parameter of coal according to claim 8 , wherein the coal is heat-treated before acquiring the solubility parameter.
10. The method for producing coke according to claim 6, The solubility parameter is the Hansen solubility parameter, In determining the blending ratio, for all combinations of two types of coal to be blended, The distance ΔHSP between the Hansen solubility parameters is 12.3 (MPa) 0.5 less than and selecting the coals to be blended so that the blended coals satisfy the above conditions.
11. The method for producing coke according to claim 6, The solubility parameter is the Hansen solubility parameter, In determining the blending ratio, for all combinations of two types of coal to be blended, The absolute value ΔLogMF of the difference between the common logarithm values of the maximum fluidity measured by the Gieseler Plastometer method is 0.67 log / ddpm or less; The absolute value ΔRo of the difference in the average maximum reflectance of vitrinite is 0.05% or more, and The distance ΔHSP between the Hansen solubility parameters is 4.2 (MPa) 0.5 below and selecting the coals to be blended so that the blended coals satisfy the above conditions.
Citation Information
Patent Citations
Production of coke for blast furnace
JP1995157769A
Method of estimating coke strength, method blending coal for coke production, method of selecting coal for coke production and coke production method
JP2014218649A
Method for evaluating inter-coal adhesion
WO2013145677A1
